THE EFFECT OF TRAINING AND COMPENSATION FOR EMPLOYEE PERFORMANCE WITH EMPLOYEE JOB SATISFACTION AS INTERVENING VARIABLES ON MSME IN SOUTH TANGERANG - Aini, Aura Qurratul; Febriyantoro, Mohamad Trio; Zulkifli, Zulkifli; Suleman, Dede; Saputra, Fendi; Suyoto, Totok (Journal of Industrial Engineering & Management Research, 2022)
Research this aim for test influence training and compensation to performance employee with satisfaction work as an intervening variable for MSME employees in South Tangerang. Study quantitative this conducted with use questionnaire through gform use scale linkert. Study using the Structural Equation Modeling model with using the Smartpls software. From the data distributed, 109 eligible respondents were collected for processed more continue. Research results show that there is influence Among training and compensation to performance employee, with satisfaction work is variable mediation which is not significant or no effect on training to performance employees, as well compensation to performance employee